A method to support accessible video authoring - Villena, Johana Maria Rosas (2016)
Human qualities are only developed in human society by means of interaction with others. Since a child is born, he/she sees, hears, touches, and tastes things. That means visual and aural stimuli are natural for human beings and these stimuli are also present on videos. Perhaps, this is the reason why videos have a huge impact on society. An evidence of the popularity of videos growing in society can be observed in the large volume of videos uploaded onto YouTube or the number of videos posted on Facebook. Besides, the rise of smartphones has increased the number of users that not only watch but also produce videos. However, what happens to people who cannot access those contents because they have disabilities or some temporary illness. To avoid excluding people from understanding video content, it is important to provide a video with accessibility. Thus, about 23.9% of the Brazil population who declared themselves with disabilities will benefit from accessible videos. Standards, laws and regulations to promote video accessibility have been developed. Research studies about accessible video players, improving captioning, resources about sign language, and implementation of the content enrichment have also been developed. In spite of the video production process being well defined, current research and market practices do not take accessibility into account as part of its stages. They do not explain how amateur authors can create alternative content following guidelines or how to incorporate accessibility guidelines to the video production process. This thesis proposes a method, called Video4All, for alternative content authoring as part of an accessible video production process. Video4All is composed by a set of activities, including alternative content guidelines, and alternative content evaluation. A case study was conducted to verify the effectiveness of applying the proposed method by amateur authors, evaluating their generated alternative content. In order to describe the process, was incorporated accessibility in all stages and the case studies reported the difficulties which users had during the interaction with an accessible video player. Additionally, the proposal involved the development of an alternative content evaluation method as a means to provide a quality measure, enabling authors to better understand the accessibility level of the alternative content they create. The accessible video production process can be used by any amateur author to improve the accessibility of their videos. Moreover, Video4All helps the authoring and evaluation of alternative content.